Mengembangkan Resiliensi Diri Santri Melalui Konseling Singkat Berfokus Solusi: Tinjauan Efektivitas dan Implikasi Praktis - Listiawati, Ludiana; Rahmatika, Zulfa; Kurnia Sari, Dita; Kurniadi, Romyzar (Counseling AS SYAMIL: Jurnal Ilmiah Bimbingan Konseling Islam, 2023)
Abstract: The purpose of this study was to determine the level of resilience of santri in pesantren using brief solution-focused counseling. This research is a quasi-experimental research using pre-test post-test control group design. The sampling technique used by researchers is purposive sampling technique. The research subjects consisted of 10 students of Al Jihad Surabaya Islamic boarding school who had low self-resilience scores based on the results of the self-resilience questionnaire. The sample was randomly divided into two groups, namely the control group and the experimental group. The data collection instruments used in this study were self-resilience questionnaire and self-reflection sheet. While the treatment instrument is a short solution-focused counseling guide. The self-resilience questionnaire was developed by the researcher based on aspects of resilience. Based on validity and reliability tests, the self-resilience questionnaire is suitable for use as a data collection tool. The data analysis technique in this study is the two independent sample test Mann Whitney U. The statistical analysis results show the Asymp.Sig. (2-tailed) is at 0.003 (0.003 <0.005), so Ho is rejected. This means that brief solution-focused counseling is proven to increase the resilience of students at Pesantren Al-Jihad Surabaya. Future research related to solution-focused brief counseling and santri self-resilience can use a variety of meeting sessions, populations, and other research designs.